Modeling and analyzing coupling noise effect of Cu-carbon nanotube composite through-silicon vias interconnects using NILT based - Ait Belaid Khaoula; Belahrach Hassan; Ayad Hassan; Ez-Zaki Fatima (Serbian Journal of Electrical Engineering, 2023)
In the modern field of microelectronics, the performance of interconnects tends to decrease as the technology node advances. Therefore, Cu-CNT composite TSV interconnects are utilized due to their favorable performance. In this article, Cu-CNT composite TSV interconnects have been studied. The objective of this work was to propose an accurate method for calculating time domain coupling noise in 3D structures based on Cu-CNT composite TSVs. The equivalent lumped element circuit, the NILT method, and the T-matrix were exploited. Throughout the study, the influence of geometric parameters, temperature, and CNT filling ratio were examined. The proposed method has been validated using PSpice results. The obtained results have shown good performance and accuracy. The average percentage error observed is less than 1 %.